Serum Levels of LL-37 and Inflammatory Cytokines in Plaque and Guttate Psoriasis - Young Ji Hwang; Ho Jung Jung; Min Jung Kim; Nam Kyung Roh; Jae Wook Jung; Yang Won Lee; Yong Beom Choe; Kyu Joong Ahn (Mediators of Inflammation)
Psoriasis is a chronic inflammatory skin disease. It is assumed that the plaque phenotype of psoriasis is associated with T helper (Th) 1 immune response activation, while the guttate phenotype is associated with the Th17 immune response. Previous investigations of differences in the serum levels of cytokines relative to the clinical psoriatic phenotype have yielded conflicting results. This study compared the levels of circulating inflammatory cytokines and LL-37 relative to the morphological phenotype in patients with psoriasis. Seventy-four age-matched patients with psoriasis (32 with guttate psoriasis and 42 with plaque psoriasis) and 12 healthy controls were included. A multiplex cytokine assay and enzyme-linked immunosorbent assay were used to measure levels of Th1- and Th17-derived cytokines and LL-37, respectively. Circulating levels of interferon- (IFN)-γ, interleukin- (IL)-1RA, IL-2, and IL-23, and LL-37 were significantly higher in patients with psoriasis than in healthy controls. However, the serum levels of inflammatory cytokines (IL-7, IL-22, and IL-23) and LL-37 did not differ significantly between the guttate and plaque phenotypes of psoriasis. There was a positive correlation between serum inflammatory cytokine levels and the Psoriasis Area and Severity Index score. The findings of this study suggest that the serum levels of inflammatory cytokines reflect the disease activity rather than determine the morphological phenotype.